Toward Artificial Peptide Nanocapsules - Wang, Yuan; Chen, Bing (Nano-Micro Letters, 2024)
Highlights: 1 The formation of peptide nanocapsules is facilitated by a gradient interface, where the differential solvent concentration drives the peptides to preferentially localize and assemble. 2 The peptide nanocapsules, characterized by their hollow structures, demonstrated potential as carriers for targeted drug delivery.